Review of Sargent's The Conquest of American Inflation - Marimon, Ramon (Journal of Economic Literature, 2000)
Sargent's book provides a reinterpretation of the US inflation record over the last half-century, reflecting on how macroeconomic theory has evolved since the beginnings of the rational expectations revolution. It is a basic reference on dynamic macroeconomic theory.